An experimental performance evaluation of Flex Banner and polypropylene fibre reinforced bituminous mixes. (2021) - Vishnuvardhan, K.; Rajkumar, R.; Navin Ganesh, V.; Cyril Santhosh, J.
Abstract: The flexible pavements used all over the world demand the use of Bituminous Mixes which have high stability, high resistance to deformation, less temperature susceptibility, high resistance to rutting and cracking. But, the bitumen material available through various sources lack the high performance quality expected of them. On the other hand, the waste materials generated everyday through various sources and which are environmentally degradable are found to have the minerals which can improve the properties of the bitumen and bituminous mixes. Similarly, various virgin polymers including Polypropylene Fibres (PF) have been used in Civil Engineering applications including in the preparation of concrete as a reinforcing material for improving its performance. In this study, the Flex Banner (FB) in shredded form was used along with PF in optimum content as a reinforcing material in bitumen for the preparation of Reinforced Bituminous Mixes (RBM). The optimum FB and PF content to be used was found to be 6% each for reinforcing the bitumen. The performance of the RBM was compared with the Conventional Bituminous Mixes (CBM) prepared with conventional bitumen (CB). The results indicated an increase in Marshall Stability and Flow values for the RBM when compared to the CBM. The study concluded that the RBM prepared with an optimum FB and PF content of 6% each can be used in the field to achieve higher service life for the flexible pavements which are also environmentally sustainable due to the use of waste materials.